1992
DOI: 10.1093/nar/20.12.2985
|View full text |Cite
|
Sign up to set email alerts
|

Multiple mRNA species generated by alternate polyadenylation from the rat manganese superoxide dismutase gene

Abstract: The mitochondrial enzyme, manganese superoxide dismutase (MnSOD) is an integral component of the cell's defense against superoxide-mediated cellular damage. We have isolated and characterized four cDNA clones and the structural gene for rat MnSOD. Northern analyses using MnSOD cDNA probes detected at least five mRNAs in all tissues and cell types examined. Southern and Northern analysis using a 3' non-coding sequence probe, common to all the cDNAs, showed hybridization only to genomic restriction fragments tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…The steady-state levels of Mn-SOD RNA are much lower in HeLa-tat cells than in the parental cells. The multiple transcripts seen have been ascribed to alternative polyadenylylation signals (34). Cu,Zn-SOD RNA levels were the same in both cell types.…”
Section: Resultsmentioning
confidence: 87%
“…The steady-state levels of Mn-SOD RNA are much lower in HeLa-tat cells than in the parental cells. The multiple transcripts seen have been ascribed to alternative polyadenylylation signals (34). Cu,Zn-SOD RNA levels were the same in both cell types.…”
Section: Resultsmentioning
confidence: 87%
“…Endogenous MnSOD mRNA Half-life-We have previously reported that the five transcripts of rat MnSOD mRNA observed on steady state Northern analysis arise from alternative polyadenylation of the primary transcript (29). Work from our laboratory has also shown that each of the mRNA species are induced and degraded similarly in response to proinflammatory mediators (14).…”
Section: Resultsmentioning
confidence: 98%
“…Plasmid Construction-MnSOD fragments were amplified by polymerase chain reaction from a previously characterized MnSOD cDNA (29) using standard conditions and primers specific to appropriate 5Ј and 3Ј termini. Products are denoted by their position relative to the translational initiation site (ϩ1) of the MnSOD cDNA (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Each of these mRNA transcripts has been shown to give rise to mature, functional protein (Hurt et al, 1992). MnSOD rnRNA levels (figure 12A) in both control and CSH-treated astrocytes increased in parallel between 0 and 12 hours foUowing initiation of the treatment.…”
Section: Northern B10ts For Mnsodmentioning
confidence: 99%